2020
DOI: 10.1515/hsz-2020-0124
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib downmodulates aggressiveness mediators of colorectal cancer (CRC): Low Molecular Weight Protein Tyrosine Phosphatase (LMWPTP), Protein Tyrosine Phosphatase 1B (PTP1B) and Transforming Growth Factor β (TGFβ)

Abstract: Colorectal Cancer (CRC) therapy confronts challenges as chemoresistance and side effects. Therefore, drugs with antitumor properties that downmodulate aggressiveness mediators are required. Studies have shown the relevance of Low Molecular Weight Tyrosine Phosphatase (LMWPTP), Protein Tyrosine Phosphatase 1B (PTP1B), and Transforming Growth Factor β (TGFβ) in mediating proliferation, chemoresistance, and metastasis. In this study, we aimed to investigate the responsiveness of colorectal cancer lines (HT29 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, TGF-β-induced resistance to AZD6244 and the BRAF inhibitor PLX4032 (vemurafenib) have also been observed in CRC cells[ 67 ]. However, another study demonstrated that vemurafenib downregulated the expression of TGF-β and p-Smad3 in HT29 CRC cells[ 105 ]. Trastuzumab, a human epidermal growth factor receptor (HER)2-targeting antibody, is the only available targeted agent for first-line palliative systemic treatment of HER2-positive esophagogastric adenocarcinoma (EAC).…”
Section: Tgf-β Signaling and Drug Resistance In Gi Cancermentioning
confidence: 99%
“…Moreover, TGF-β-induced resistance to AZD6244 and the BRAF inhibitor PLX4032 (vemurafenib) have also been observed in CRC cells[ 67 ]. However, another study demonstrated that vemurafenib downregulated the expression of TGF-β and p-Smad3 in HT29 CRC cells[ 105 ]. Trastuzumab, a human epidermal growth factor receptor (HER)2-targeting antibody, is the only available targeted agent for first-line palliative systemic treatment of HER2-positive esophagogastric adenocarcinoma (EAC).…”
Section: Tgf-β Signaling and Drug Resistance In Gi Cancermentioning
confidence: 99%